THE EFFECT OF VOLUNTARY DISCLOSURE PROGRAM, TAX SANCTIONS AND TAX AUDIT ON TAXPAYER COMPLIANCE CASE STUDY OF BATAM CITY TAXPAYER - Sari Dewi; Paskaris Paskaris (Universitas Internasional Batam, 2024)
Taxpayer compliance is the availability of a person to pay tax rights and obligations accompanied by established rules, which is the responsibility of every taxpayer to comply. The research was carried out with the aim of knowing taxpayer compliance with taxpayer awareness as a moderation that is influenced by the variables of tax disclosure, tax sanctions, and tax audits. The sample from this study is the obligatory tax registered at the Batam City Tax Service Office, where the sample is taken as many as 240 data with test data processed using SmartPLS 3.2.9 software. The test data obtained in this study, namely the direct test, shows that taxpayer compliance is positively and significantly affected by tax sanctions, while tax audits and voluntary disclosure programs have no significant effect. The direct test also shows that taxpayer awareness moderates tax sanctions and tax audits on taxpayer compliance. However, taxpayer awareness does not moderate the voluntary disclosure program's relationship to taxpayer compliance.